2018
DOI: 10.1177/0734282917749682
|View full text |Cite
|
Sign up to set email alerts
|

Reliability, Factor Structure, and Measurement Invariance of a Web-Based Assessment of Children’s Social-Emotional Comprehension

Abstract: The purpose of this study was to evaluate the psychometric properties and measurement invariance of a web-based, self-administered battery of assessments of social-emotional comprehension called "SELweb." Assessment modules measured children's ability to read facial expressions, infer others' perspectives, solve social problems, delay gratification, and tolerate frustration. In an ethnically and socioeconomically diverse sample of 4,419 children in kindergarten through third grade who completed SELweb: (a) sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…Cronbach's α for SELweb's social–emotional composite score was 0.89. Individual modules demonstrated Cronbach's alphas between 0.73 and 0.88 and were similar in magnitude to internal consistency reliabilities found in two large studies with GenEd students (McKown, ; McKown et al, ; Table ).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Cronbach's α for SELweb's social–emotional composite score was 0.89. Individual modules demonstrated Cronbach's alphas between 0.73 and 0.88 and were similar in magnitude to internal consistency reliabilities found in two large studies with GenEd students (McKown, ; McKown et al, ; Table ).…”
Section: Resultssupporting
confidence: 65%
“…The current sample was too small to estimate factor loading with confirmatory factor analysis. Instead, estimated factor loadings from the SELweb norming sample were used (McKown, ).…”
Section: Methodsmentioning
confidence: 99%
“…We conceptualize each of the four dimensions of social-emotional comprehension SELweb assesses as a partially independent component of social-emotional comprehension. That conceptualization is supported by two empirical studies showing an excellent fit of the data to a fourfactor confirmatory model in which ER, social perspective-taking, social problem-solving, and self-control are modeled as correlated latent variables (McKown et al, 2016;McKown, 2019). Together, SELweb's modules provide broad construct coverage of distinct but interrelated dimensions of social emotional comprehension.…”
mentioning
confidence: 74%
“…Previous research examining all of SELweb modules together has described its psychometric properties, including evidence of structural validity, and discriminant, convergent, and criterion-related validity (McKown et al, 2016). In addition, using a confirmatory factor analysis approach, (McKown, 2019) reported that SELweb’s five modules demonstrated configural, metric, and partial scalar invariance across sex and ethnicity. The confirmatory models in that measurement equivalence study used total scores from the five modules as indicators of latent constructs.…”
mentioning
confidence: 99%
“…One notable exception is the recent evaluation of SELweb , a web-based, self-administered battery of assessments of social–emotional comprehension. McKown’s (2019b) analyses begin with an investigation of psychometric properties and measurement invariance to determine whether the measures are culturally or contextually biased. This involved examining the assumption that the constructs associated with emotion recognition, social perspective-taking, and social problem-solving hold similar meanings across ethnically and socioeconomically diverse students in urban and suburban schools.…”
Section: The Need To Measure Up: Examining the Adequacy Of Existing S...mentioning
confidence: 99%